Exploring the Phenomenon of Missing Girls in the South Caucasus - World Bank (Washington, DC, 2015)
Sex ratio at birth, the number of boys born for every 100 girls, has increased in the South Caucasus in the past decades. A World Bank study sought to produce rigorous and supporting evidence on the issue of “missing girls” in the South Caucasus countries of Armenia, Azerbaijan, and Georgia to inform and propose policy options. The findings highlight the causes and consequences of skewed birth ratios and sex selection and are summed up in this brief. Although recent data suggest an improving trend, the higher-than-expected ratio of male to female births reveals underlying gender inequality in the region- overshadowing progress in other areas, such as educational attainment. The specific topics addressed in this paper are: the preference for sons, decline in fertility, prenatal sex detection technology, and shocks due to the dropping rates. Finally the report concludes by discussing policies that could be put in place to address the current trend in sex ratio in the Caucasus.